Hummingbirds - McCarter, James; Proctor, Noble S. (Dorset Press, 1989)
Poetic quotations accompany full-page photographs of various hummingbirds.
Keywords: Hummingbirds; Pictorial works; Pictorial works; Photography of birds; Birds; dept.bio

Garden Birds: How to Attract Birds to Your Garden - Proctor, Noble S.; Walker, Cyril Alexander; Parmenter, Tim (Rodale Press, 1986)
Includes a directory of 100 birds, describing their migration, habitat, scientific name, and physical characteristics.
Keywords: Bird attracting; Garden animals; dept.bio; faculty_collection

Pesticide residues in Arizona peregrine falcon eggs and prey - Ellis, D.H.; DeWeese, L.R.; Grubb, T.G.; Kiff, L.F.; Smith, D.G.; Jarman, W.M.; Peakall, D.B. (Bulletin of Environmental Contamination and Toxicology, 1989)
11 citations (Crossref) [2023-10-31]
Keywords: 1; 1 dichloro 2; 2 bis(4 chlorophenyl)ethylene; Animal; Arizona; Birds; DDE; DDT; Egg Shell; Pesticide Residues; USA; Arizona; bird; chlorphenotane; dept.bio; dieldrin; egg; eggshell thinning; endrin; falcon; hexachlorobenzene; hexachlorocyclohexane; nonhuman; organochlorine; oxychlordane; peregrine; pesticide; polychlorinated biphenyl; residue analysis; united states; wildlife